“Unbind Him and Let Him Go” (JN 11:44): Ethical Issues in the Determination of Proportionate and Disproportionate Treatment - Shannon, Thomas A. (Theological studies (Baltimore), 2008)
The article (1) reviews a variety of magisterial documents and essays concerning the terms “morally ordinary” and “extraordinary” treatment in relation to the provision of assisted nutrition and hydration, particularly for patients in a “permanent vegetative state”; (2) considers how the terms “ordinary” and “extraordinary” are used in both the moral and medical contexts, the process by which they are defined, and how economic issues relate to moral analysis; and (3) argues that the content of the terms is changing as well as the method to determine whether a treatment is ordinary or extraordinary.